2020
DOI: 10.55461/svks9397
|View full text |Cite
|
Sign up to set email alerts
|

Blind Prediction of Shaking Table Tests of a New Bridge Bent Design

Abstract: Considering the importance of the transportation network and bridge structures, the associated seismic design philosophy is shifting from the basic collapse prevention objective to maintaining functionality on the community scale in the aftermath of moderate to strong earthquakes (i.e., resiliency). In addition to performance, the associated construction philosophy is also being modernized, with the utilization of accelerated bridge construction (ABC) techniques to reduce impacts of construction work on traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Although these systems have significant potential for enhanced seismic response, they can only be fully utilized if they can be modeled and their response can be properly predicted in the design phase of bridges. A blind prediction competition recently conducted by the Pacific Earthquake Engineering Research (PEER) Center from the shaking table test of the second system (Nema, 2018;Günay et al, 2020) demonstrated a large variation of the response predictions by researchers and practitioners. Therefore, there is an essential need to characterize the seismic response of these enhanced feature systems and improve their modeling and response predictions.…”
Section: Problem Statement and Objectivesmentioning
confidence: 99%
“…Although these systems have significant potential for enhanced seismic response, they can only be fully utilized if they can be modeled and their response can be properly predicted in the design phase of bridges. A blind prediction competition recently conducted by the Pacific Earthquake Engineering Research (PEER) Center from the shaking table test of the second system (Nema, 2018;Günay et al, 2020) demonstrated a large variation of the response predictions by researchers and practitioners. Therefore, there is an essential need to characterize the seismic response of these enhanced feature systems and improve their modeling and response predictions.…”
Section: Problem Statement and Objectivesmentioning
confidence: 99%